Modern atomic absorption spectrometry: achievements and future prospects - Volynsky, A.B. (Украинский химический журнал, 2005)
Modern trends in development of various branches of atomic absorption spectrometry (AAS) are discussed. Most important direction seems to be further development of multi-element AAS and its wider introduction into practice. Widespread of hydride generation AAS to the elements that does not form volatile hydrides (such as Rh, Mn, Cd, etc.) is of interest from viewpoint of development of extremely sensitive methods of analysis and of general chemistry. Although basics of electrothermal AAS are mostly formulated as well, further works in chemical modifiers and development of the methods of direct analysis of solids are still actually. Very important point of activity of specialists in AAS is wider application of their achievements in the practice of service laboratories, via wider introduction of the corresponding methods to international and national standards. Обсуждены современные тенденции развития различных областей атомно-абсорбционной спектрометрии (AAC). Предполагается, что наиболее важным направлением является развитие многоэлементной AAC и ее более широкое использование в практике. Применение методологии ААС с генерацией гидридов к элементам, которые не образуют летучие гидриды (Rh, Mn, Cd, и т.д.), является интересным при разработке чрезвычайно чувствительных методов анализа. Остаются актуальными работы по химическим модификаторам и разработка методов прямого анализа твердых проб. Важным является более широкое внедрение этих достижений в практику работы сервисных лабораторий за счет введения методов ААС в международные и национальные стандарты. Обговорено сучасні тенденції розвитку різних галузей атомно-абсорбційної спектроскопії (ААС). Найбільш важливим напрямком є розвиток багатоелементної ААС та її більш широке використання у практиці. Застосування методології ААС з генерацією гідридів до елементів, що не утворюють летючі гідриди (Rh, Mn, Cd та ін.), є цікавим при розробці надчутливих методів аналізу. Актуальними залишаються роботи по хімічним модифікаторам і розробці методів прямого аналізу твердих проб. Важливим є більш широке впровадження цих досягнень у практику роботи сервісних лабораторій за рахунок введення методів ААС у міжнародні та національні стандарти.